MOTIVATING SECONDARY SCHOOL STUDENTS TO LEARN GRAMMAR THROUGH GAME-BASED STUDENTS RESPONSE SYSTEMS (GSRS) APPLICATION : STUDENTS’ PERCEPTION IN INDONESIA - Nurhayati, Hekmah Nurhayati (Faculty of Teaching and Education, University of August 17, 1945, Banyuwangi, 2023)
The present study aimed to perceive students’ perception in learning grammar through GSRS in secondary schooling context in Indonesia. GSRS can help the students to boost their engagement and motivation. Qualitative case study was used as research design. 12 students participated in this study. They were selected by using purposive random sampling. Questionnaire and interview were used to collect the data regarding students’ perception in using Kahoot application. The questionnaire comprises 20 questions and the interview consists of 9 questions. The collected data were analyzed quantitatively. The findings of the study showed that the students’ responses toward Kahoot! Application use in learning grammar were positive. The students felt enjoyable during the class (75%) and they were motivated to learn tenses or grammatical point (58,3%). Another finding found is Kahoot! could reduce the boredom of learning process in grammar class (58,3%). While Kahoot! Application provided positive impact on students’ motivation in learning grammar, the sudentts also experienced challenges in learning grammar during the class such as unstable network and limited time to response the questions. The study empirically shows that students’ perception toward Kahoot! application in learning grammar is positive. It can encourage secondary school students to learn grammar more enjoyable.